Spectral Engineering for Optimal Signal Performance in the Microwave SQUID Multiplexer - Salum, Juan Manuel (2024)
We describe a technique to optimize the dynamic performance of microwave SQUID multiplexer (µMUX)-based systems. These systems proved to be adequate for reading out multiple cryogenic detectors simultaneously. However, the requirement for denser detector arrays to increase the sensitivity of scientific experiments makes its design a challenge. When modifying the readout power, there is a trade-off between decreasing the signal-to-noise ratio (SNR) and boosting the nonlinearities of the active devices. The latter is characterized by the spurious free dynamic range (SFDR) parameter and manifests as an increment in the intermodulation products and harmonics power. We estimate the optimal spectral location of the SQUID signal containing the detector information for different channels. Through the technique, what we refer to as Spectral Engineering, it is possible to minimize the SNR degradation while maximizing the SFDR of the detector signal, thus, overcoming the trade-off.